The Criticism of Ibn Dorade About The Specialist Language - Ahmed Isaʼa Taher ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study sheds the light on an important important linguistic phenomenon. According to the dictionary of (Jamharat Al-Lughah) to his classified work, Ibn Dorade (325H). It is a phenomenon of the criticism linguistic which is made clear of the essential sections and its chapters to the book and the research has dealing with the criticisms of the classified work. And his opinions about the especially linguistic as a track the linguistic using to the greatest linguists, poets, novelists, spoken men and others. The researcher has read the rules to the workbook in his opinions to groups of certain criteria like listening, measurements, and the opinions of the linguistic experience and their listening criteria and morphology. And the area to his criticisms of the researcher has been ranging manifestations as a singular, plural and the most appropriate the spatial and the evidence, poetic rhythm and the generated. But the approach which is taken by this research is approach that is depended on the analysis and description.